TATA KELOLA DIGITAL SISTEM PENGGAJIAN BERBASIS KINERJA PADA PEGAWAI PEMERINTAH KABUPATEN MAHAKAM ULU - Hipui, Maria Vianei; Fitriati, Rachma (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In Indonesia, personnel management in local governments, including payroll, is still often done manually or semi-automatically. This manual payroll management causes various problems, including payment delays, salary calculation errors, and lack of transparency in the payroll process. The government of Mahakam Ulu Regency, one of the regions in East Kalimantan Province, faces similar challenges. Amid efforts to accelerate regional development, the local government adopted a digital technology-based payroll system to build a more transparent, measurable, and fair payroll system. This study uses a qualitative approach with data collection through in-depth interviews, focus group discussions, observation, and literature study. The study results show the need to develop performance-based digital payroll systems regulations by issuing a circular letter to the Mahakam Ulu District Government. This circular serves as a guiding framework for integrating the digital system into personnel management, emphasizing responsibilities among stakeholders, and ensuring the application of meritocratic principles in performance appraisal and incentives. This digital governance model ensures that salaries are paid on time and follow regulations. It assesses employee performance based on clear, more modern, responsive parameters to support improved productivity and performance